Respon Pertumbuhan dan Produksi Tanaman Mentimun (Cucumis sativus L.) dengan Pemberian Pupuk Kandang Sapi dan Pupuk NPK - Gulo, Irene; Zulfida, Ida; Dewi, Dora Silvia (UNIVERSITAS LABUHANBATU, 2025)
This study aimed to determine the effect of cow manure and NPK fertilizer, both individually and in combination, on the growth and yield of cucumber plants (Cucumis sativus L.). The experiment was conducted using a factorial Randomized Block Design (RBD) with two factors: cow manure (0, 1, 2, and 3 kg/plot) and NPK fertilizer (0, 60, 80, and 100 g/plot), each replicated three times. The observed parameters included plant height, number of leaves, number of fruits per plant, total fruit weight per plot, and fruit length. Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level. The results showed that the interaction between cow manure and NPK fertilizer had no significant effect on all observed parameters. However, on average, the combination treatment of 2 kg cow manure and 100 g NPK fertilizer produced the best results across all growth and yield parameters of cucumber plants. Cow manure contributed to improving soil structure and fertility, while NPK fertilizer supplied essential macronutrients required by the plants. Keywords: Cucumis sativus L., cow manure, NPK fertilizer